Adaptive load balancing algorithm for wireless distributed computing networks - Alfaqawi, Mohammed; Habaebi, Mohamed Hadi; Siddiqi, Mohammad Umar; Islam, Md. Rafiqul; Khan, Sheroz; Datla, Dinesh (Institute of Electrical and Electronics Engineers, Inc., 2016)
The concept of wireless distributed computing (WDC), proposed recently, is used to distribute and allocate computational tasks wirelessly. Despite various benefits of WDC, such as distributing the workload efficiently among cooperating nodes, WDC concept is facing enormous challenges. Proposing an efficient task allocation algorithm is one of the key challenges in WDC network. The work reported here proposes a novel task allocation algorithm called as adaptive load balancing (ALB). The ALB algorithm nominates the cooperating nodes in WDC network adaptively based on the channel conditions among the cooperating nodes. Then, it balances the workload amongst the cooperating nodes based on the available energy in each node. Herein, the validity of the proposed novel ALB algorithm is proved first. Then, ALB algorithm is applied to an application in cognitive radio network (CRN). Furthermore, the channel impact on the distributed tasks by ALB algorithm, in WDC-CRN, is investigated and benchmarked. Accordingly, the probability of detection results in case of applying the novel ALB algorithm is found to be enhanced.